THE SPATIO-TEMPORAL FEATURE OF FROSTS IN THE SOUTH OF WESTERN SIBERIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The results of the meteorological data analysis for a 20-year period in the southern taiga and subtaiga of Western Siberia showed a spatio-temporal variability in the duration and intensity of frosts. The highest probability is recorded throughout the territory in the first decade of May (from 70% to 90%) and falls at the beginning of the growing season of agricultural plants. The probability decreases to an average of 40% to the end of May, The probability of frost is about 10% in the first decade of June for the North-Western part of the study area. In the region as a whole, frosts they cause significant risks to the sustainable functioning of the local crop production system. Against the background of an increase in the duration of the active growing season, there is a high probability of frost in subsequent years.
Keywords: frosts; frost-free period; Western Siberia; dangerous climatic phenomena